Elements Hindering Vietnamese Tertiary Students’ Participation in Group Activities: A Case Study - Lien Thi My Tong (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
Plenty of meticulous research has been conducted to investigate the entire process for implementing group activities in language classrooms. Nevertheless, few detailed empirical investigations have been pursued in the sub-area of what influences the participation of English-as-a-Foreign-Language (EFL) students in group discussions. Thus, the present study was conducted to examine the elements impacting the group-work participation of first-year EFL students at University of Languages and International Studies (ULIS), Vietnam National University (VNU). Ten EFL freshmen and four teachers of English participated in the study over a four-week period by attending semi-structured interviews. The findings highlighted a variety of elements discouraging the learners’ participation related to themselves, pedagogy, and culture and also revealed internal elements as the most significant.